Demografia e diversidade genética de onça-parda (Puma concolor) e jaguatirica (Leopardus pardalis) da Estação Ecológica de Caetetus SP e sua importância para a conservação desses felinos - Saranholi, Bruno Henrique (2013)
The loss and fragmentation of habitat due to intensive human intervention are the main threats to natural populations. Species with low density and large home range, like felids, are the most threatened species by these changes. In an attempt to minimize this impact, detection of population density and genetic characterization are necessary to propose conservation measures. Thus, the main objective of this study was to characterize the populations of two species of felines, cougars (Puma concolor) and ocelots (Leopardus pardalis) of Caetetus Ecological Station (EEC - SP, one of the last remnants of Atlantic Forest within the state of São Paulo), about their demographic and genetic characteristics from non-invasive samples (feces and hairs).We collected the samples on EEC tracks and identified the species, individualized each sample, sexed each individual and calculated the genetic diversity of the population using molecular markers. Abundance was estimated from the capture-recapture historic, with opened and closed population models. We identified 17 samples of feces cougar and 12 of ocelot. Of these samples, six individuals were individualized as cougar and five as ocelot, these numbers represent the minimum population sizes for the entire sample period (18 months). The values of abundance and density estimated using the model of closed population was more similar to that found in genetic individualization, five individuals for each species and densities of 4.92/100 km2 (P. concolor) and 19.51/100 km2 (L. pardalis). The genetic diversity of the two species was lower than that from other studies, probably due the landscape´s fragmentation, which reduces the gene flow with others populations. Also, the genetic diversity for L. pardalis was lower than P. concolor, which is possibly related to the ocelot behavior of avoid opened and disturbed areas, which can reduce the potential for gene flow. Furthermore, we also observed structure of P. concolor from EEC with populations from other locations, but we also identified gene flow, including relatedness. Thus, the results of genetic diversity and demographics demonstrate the importance of the Ecological Station Caetetus for these species and also underscores the importance of establishing measures to enable the viability of its populations over long term, as facilitating gene flow with individuals from others locations.